PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MCDONALDS PONDOK AREN TANGERANG - Suhendar; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of leadership style and work discipline on employee performance at Mcdonalds Pondok Aren Tangerang, both partially and simultaneously. The method used is quantitative. The sampling technique used Slovin sampling and the sample obtained in this study was 50 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are a discussion of the influence of leadership style (X1) and work discipline (X2) on employee performance (Y), as follows: leadership style (X1) has a significant effect on employee performance (Y) with the regression equation Y = 12.614 + 0.645 X1, the correlation coefficient value is 0.600 where the value is in the interval 0.600-0.799, meaning that the two variables have a strong level of relationship. The determination value is 35.9%. Hypothesis testing obtained a value of tcount > ttable or (value 5.190 > 2.010). Thus, H0 is rejected and H1 is accepted, this shows that there is a significant influence between leadership style (X1) on employee performance (Y). Work discipline (X2) has a significant effect on employee performance (Y) with the regression equation Y = 15,954 + 0.473 The determination value is 31.7%. Hypothesis testing obtained a value of tcount > ttable or (4.719 > 2.010). Thus, H0 is rejected and H2 is accepted, this shows that there is a significant influence between work discipline (X2) on employee performance (Y). Leadership style (X1) and work discipline (X2) have a significant effect on employee performance (Y) with the regression equation Y = 10.711 + 0.438X1 + 0.212 X2. The correlation coefficient value is 0.621 where the value is in the interval 0.600-0.799, meaning that the two variables have a strong level of relationship. The determination value is 38.6%. Hypothesis testing obtained a value of fcount > ftable or (14,757 > 3,200). Thus, H0 is rejected and H3 is accepted, this shows that there is a significant simultaneous influence between leadership style (X1) and work discipline (X2) on employee performance (Y).